Research in Surfactant Effect on Promoting Gas Hydrates Formation - Xie Yubo; Yang Liang; Liu Daoping; Yang Meng (Zhileng xuebao)
Nowadays, natural gas hydrates are recognized as an important future energy in 21 Century. Pressure, temperature, the contact area of gas and water, surfactant and other factors affect its formation. The basic properties of the surfactant are introduced in the present paper, and the effects of surfactant on the formation of hydrates are summarized from the changes of surface tension of liquids for gas hydrates formation, micelle formation and the hydrate morphology. The mechanism of surfactant promoting gas hydrates formation is then put forward. In order to form a unified understanding on hydrate formation mechanism, the hydrate form is not only observed, the influence of the surfactant on the formation of the hydrate is also analyzed from the internal structure of the hydrate film for the future research.